Justice, Health, and Healthcare - Norman Daniels (The American Journal of Bioethics 2001, Volume 1, Number 2, 2001)
Healthcare (including public health) is special because it protects normal functioning, which in turn protects the range of opportunities open to individuals. I extend this account in two ways. First, since the distribution of goods other than healthcare affect population health and its distribution, I claim that Rawls's principles of justice describe a fair distribution of the social determinants of health, giving a partial account of when health inequalities are unjust. Second, I supplement a principled account of justice for health and healthcare with an account of fair process for setting limits or rationing care. This account is provided by three conditions that comprise accountability for reasonableness.